2022
DOI: 10.1042/bst20211252
|View full text |Cite
|
Sign up to set email alerts
|

GCN2: roles in tumour development and progression

Abstract: GCN2 (general control nonderepessible 2) is an eIF2α kinase responsible for entirely rewiring the metabolism of cells when they are put under amino acid starvation stress. Recently, there has been renewed interest in GCN2 as a potential oncotarget, with several studies reporting the development of small molecule inhibitors. The foundation of this work is built upon biochemical and cellular data which suggest GCN2 may be aberrantly overexpressed and is responsible for keeping cells on ‘life-support’ while tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…In human cells, there are two major regulatory mechanisms for amino acid sensing, including GCN2 and mTOR signalling pathways 21 . In response to decreased amino acid levels or inhibited ARSs, GCN2 kinase binds tightly to uncharged tRNA to stimulate its autophosphorylation, resulting in up‐regulation of ATF4 to induce gene expression essential for amino acid metabolism 22 . Inhibition of EPRS significantly stimulates GCN2 phosphorylation, which is abrogated by proline 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In human cells, there are two major regulatory mechanisms for amino acid sensing, including GCN2 and mTOR signalling pathways 21 . In response to decreased amino acid levels or inhibited ARSs, GCN2 kinase binds tightly to uncharged tRNA to stimulate its autophosphorylation, resulting in up‐regulation of ATF4 to induce gene expression essential for amino acid metabolism 22 . Inhibition of EPRS significantly stimulates GCN2 phosphorylation, which is abrogated by proline 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition of protein production allows the cell to upregulate autophagy or modulate other feedback loops to maintain homeostasis. Increased GCN2 levels have been shown to promote immunologic tolerance, thus making immunotherapy ineffective or less effective (41,59,60). Our results suggest that the responders' cancers were not able or as e cient at upregulating stress responses and thus the tumor cells were more susceptible to cell death under metabolic stress.…”
Section: Discussionmentioning
confidence: 99%
“…53BP1, DAG Lipase β, GCN2, AKT Ser473, and PKCzeta Thr410/403 were decreased in the microdissected tumor specimens metastatic to lymph node (patients 1, 6, and 8) post-PIKTOR. 53BP1 and AKT Ser473 help drive DNA repair (39,40) while GCN2 reduction prevents cells from upregulating metabolic stress responses (41). DAG Lipase β activity is increased in macrophages and immune cells (42,43).…”
Section: Decreased Stress Response and Immune Tolerance In Responders...mentioning
confidence: 99%
“…Hence, it was not fully convincing to explain why pulmonary vessels were more susceptible to EIF2AK4 mutations. GCN2 is an eIF2α kinase responsible for entirely rewiring the metabolism of cells in response to amino acid starvation stress, and it has been demonstrated that >10% of cancer cell lines appear to be dependent on GCN2 ( Saavedra-García et al., 2021 ) ( Gold and Masson, 2022 ). The factors in the lung environment that trigger the disease require further longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%